Unstructured spare time as an international predictor of adolescent crime - David Buil-Gil; Christopher Birkbeck; Dirk Enzmann; Karin Arbach; Marina Rezende Bazon; Muhamed Budimlić; Danielle T. Cooper; Marta Dąbrowska; Esther Fernández-Molina; Carolyn Gentle-Genitty; Aurea E. Grijalva-Eternod; Ewa M. Guzik-Makaruk; et al. (PLoS ONE, 2026)
This study investigates whether unstructured spare time is a significant correlate of self-reported offending among adolescents in multiple countries. Drawing on survey data from 58,425 13-to-17-year-olds in 21 countries in Europe, North America, and South America, we examine whether time spent in unstructured out-of-home and at-home activities, as well as structured time at home, is associated with offending prevalence and incidence. Using multivariate models that control for key criminological predictors, we find that unstructured out-of-home spare time is a robust and consistent correlate of self-reported offending. Its estimated association is larger than that of most classical predictors. While structured spare time at home is associated with lower levels of offending, unstructured spare time, particularly out-of-home, is strongly linked to both prevalence and incidence of crime involvement. Country-specific analyses reveal that this pattern holds across most national samples. Simulation analyses suggest that modest reductions in unstructured out-of-home spare time may be associated with lower levels of adolescent offending. These findings indicate that unstructured time environments constitute a cross-culturally robust correlate of adolescent offending, with potential relevance across dispositional and opportunity-based explanations, and with implications for how prevention frameworks conceptualize adolescents’ everyday environments.